The Flower of the Mind - Meynell, Alice, 1847-1922 (Salt Lake City, UT : Project Gutenberg, 2000)
"The Flower of the Mind" by Alice Meynell is a collection of poetry written in the late 19th century. It serves as an anthology that curates some of the best English poems across generations, selecting works for their quality rather than subject matter. This collection draws from a wide array of poets, showcasing timeless themes and sentiments that resonate through the ages. The opening of this anthology presents a thoughtful introduction by Meynell, who reflects on the complexities involved in creating an anthology of high-quality poetry. She articulates the challenge of making selections with both authority and personal taste, emphasizing the responsibility of the anthologist to honor the collective wisdom of literary tradition. Meynell discusses the criteria for inclusion and exclusion, touching on the fluctuation of critical opinion over time and the rarity of truly great poetry. As she sets the stage for her collection, readers are invited to appreciate the skill and artistry of the poems that will follow, which are paths through the varying landscapes of English literature. (This is an automatically generated summary.)
Release date is 2000-02-01
Transcribed from the 1898 Grant Richards edition by David Price
Keywords: English poetry